Perfluorooctane sulfonate induced toxicity in embryonic stem cell-derived cardiomyocytes via inhibiting autophagy-lysosome pathway. (December 2020) - Liu, Dan; Liu, Nuo-Ya; Chen, Li-Ting; Shao, Ying; Shi, Xiao-Meng; Zhu, Dan-Yan
Abstract: Perfluorooctane sulfonate (PFOS), a classic environmental pollutant, is reported to cause cardiotoxicity in animals and humans. It has been demonstrated that PFOS exposure down-regulates expression of cardiac-development related genes and proteins. However, the related mechanism of PFOS has not been fully elucidated. In the present study, the embryonic stem (ES) cells-derived cardiomyocytes (ESC-CMs) was employed to investigate PFOS-mediated mechanism in developmental toxicity of cardiomyocytes. Our previous study shows that PFOS induces cardiomyocyte toxicity via causing mitochondrial damage. Nevertheless, the underlying mechanism by which PFOS affects the autophagy-related mitochondrial toxicity in ESC-CMs remains unclear. Here, we found that PFOS induced the swelling of mitochondria and the autophagosome accumulation in ESC-CMs at 40 μM concentration. PFOS increased the levels of LC3-II, p62, and ubiquitinated proteins. PFOS also induced an increase of LC3 and p62 localization into mitochondria, indicating that mitophagy degradation was impaired. The results of autophagic flux using chloroquine and RFP-GFP-LC3 analysis showed that the accumulation of autophagosome was not caused by the formation but by the impaired degradation. PFOS was capable of blocking the fusion between autophagosome and lysosome. PFOS caused dysfunction of lysosomes because it down-regulated Lamp2a and cathepsin D, but it did not induced lysosome membrane permeabilization. Meanwhile, PFOS-mediated lysosomal function and the inhibitory effect of autophagic flux could be reversed by PP242 at 40 nM concentration, an mTOR inhibitor. Furthermore, PP242 restored PFOS-induced ATP depletion and mitochondrial membrane potential. In conclusion, PFOS induced mitochondrial dysfunction via blocking autophagy-lysosome degradation, leading to cardiomyocyte toxicity from ES cells. Highlights: PFOS affects the autophagy-related mitochondrial toxicity in ESC-CMs . PFOS was capable of blocking the fusion between autophagosome and lysosome. PFOS caused dysfunction of lysosomes, but did not induced lysosome membrane permeabilization. PFOS-mediated lysosomal function and the inhibitory effect of autophagic flux could be reversed by PP242.